Efficient radio resource allocation in SDN/NFV based mobile cellular networks under the complete sharing policy. Issue 3 (1st May 2018) - Vassilakis, Vassilios G.; Moscholios, Ioannis D.; Logothetis, Michael D.
Abstract : Novel networking paradigms, such as software‐defined networking (SDN) and network function virtualisation (NFV), introduce new opportunities in the design of next‐generation mobile networks. The present work investigates the benefits of the emerging SDN and NFV technologies on the radio resource management (RRM) in mobile cellular networks. In particular, the aim of the proposed RRM scheme is to enable an efficient and flexible radio resource allocation in order to assure quality of experience of mobile users. The authors consider the orthogonal frequency division multiple access scheme and the complete radio resource sharing policy. To enable time‐ and space‐efficient resource allocation, the authors investigate the applicability of the well‐known Kaufman–Roberts recursion in the context of new architectural and functional changes of SDN/NFV based mobile environments. Finally, they discuss the applicability of the proposed approach for more complicated resource sharing policies.